2013
DOI: 10.3390/ijms140918407
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Orostachys japonicus A. Berger Inhibit the Invasion of LnCaP Prostate Carcinoma Cells by Inactivating Akt and Modulating Tight Junctions

Abstract: Tight junctions (TJs) are a mode of cell-to-cell adhesion in epithelial or endothelial cells, and serve as a physical barrier to maintenance of homeostasis in body by controlling paracellular transport. Claudins are the most important molecules of the TJs, but paradoxically these proteins are frequently over-expressed in cancers and their overexpression is implicated in the invasive potential of cancer. Hence, we investigated the effects of flavonoids extracted from Orostachys japonicus A. Berger (FEOJ) on TJs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
1
14
0
1
Order By: Relevance
“…In vivo skin penetration studies with human volunteers showed that flavonoids were not only absorbed at the skin surface, but also penetrated into deeper skin layers . Flavonoids have been shown to inhibit invasion and migration of prostate carcinoma and glioblastoma cells, respectively by suppressing the AKT pathway . In a previous study we demonstrated that the flavonoid luteolin is able to suppress AKT‐signalling in both the primary MET1 and metastatic MET4 cSCC cells and could therefore be used as a therapy to inhibit AKT .…”
Section: Discussionmentioning
confidence: 93%
“…In vivo skin penetration studies with human volunteers showed that flavonoids were not only absorbed at the skin surface, but also penetrated into deeper skin layers . Flavonoids have been shown to inhibit invasion and migration of prostate carcinoma and glioblastoma cells, respectively by suppressing the AKT pathway . In a previous study we demonstrated that the flavonoid luteolin is able to suppress AKT‐signalling in both the primary MET1 and metastatic MET4 cSCC cells and could therefore be used as a therapy to inhibit AKT .…”
Section: Discussionmentioning
confidence: 93%
“…Claudin proteins have been targeted as a means of modulating TJ function. Tight junctions in human prostate cells can be modulated successfully, as shown by a study suggesting that flavonoids extracted from Orostachys japonicus A. Berger suppressed cancer migration and invasion by tightening TJs through the suppression of claudin expression, and by suppressing MMPs in LNCaP human prostate cancer cells, which at least in part resulted from the suppression of the PI3K/Akt signaling pathway (44).…”
Section: Discussionmentioning
confidence: 99%
“…Orostachys japonicus A. Berger (Crassulaceae) (OJ), also known as Wa-song in Korea, is used as a folk medication; its main habitat is on the surface of mountain rocks in Korea and Japan. OJ is a medicinal plant with immunoregulatory, anti-febrile, antidote, and anticancer activities (Jin Kwon and Kwangsoo Han, 2004;Kim et al, 2011;Lee et al, 2011;Ryu et al, 2014;Ryu et al, 2012;Shin et al, 2013;Yoon et al, 2000). It is reported that OJ increased CD4-and CD8-T cells and the production of interferon γ in BALB/c mice (Jin Kwon and Kwangsoo Han, 2004).…”
Section: Introductionmentioning
confidence: 95%